"Ion Pool" Structural Ion Storage Device: A New Strategy to Collect Ions by Nanoconfinement Effects. Issue 38 (18th August 2021) - Wang, Yuting; Chen, Huaxiang; Jiang, Jiaqiao; Zhai, Jin
Abstract: Ion storage structure widely exists in organisms, which is used to harvesting energy in environment and converting it into ion concentration gradient to maintain complex life activities. The construction of ion storage structures relies on isolating the biological body fluids by biofilm systems, which can also be regarded as local ions confinement. Mimicking this ions storage process, an "ion pool" structural ion storage device is proposed in this research by artificial ion nanochannels, which can transform the electric power into ion concentration gradient. It is consisted of micrometer‐sized ions reservoir and nanosized ions filters. Ions can be isolated within the "pool" and performed ultrahigh ions enrichment or depletion behavior deviated from bulk. Through numerical simulation by Poisson–Nernst–Planck equations, "ion pool" structural device achieves nearly 20 000 rectification ratio with low surface charge. An "ion pool" structural ions storage device is also constructed with block copolymer and polyethylene terephthalate composite membranes, a super high rectification ratio of 3184.0 is achieved from the experiment, which is the highest reported so far. The ion storage efficiency of the device reaches 14.90%, which is an order of magnitude better than non‐"ion pool" structural nanofluid devices. Abstract : Inspired by ions storage process in organisms, an "ion pool" structural ion storage device is proposed through artificial nanochannels. Ions could be isolated within the "pool" and performed ultrahigh ions enrichment or depletion behavior. Its numerical simulated rectification ratio reaches nearly 20 000 with low surface charge. The experimental prepared nanofluidic device achieves 3184.0 rectification ratio and 14.90% ion storage efficiency.